Aplicabilidade das linguagens documentárias e das leis de Ranganathan nos serviços de streaming de música - Sousa, Renato Camilo Aguiar de (2023)
This work deals with the use of Documentary Languages (LD) in music streaming services, based on the analysis of the relationship between the Five Laws of Librarianship created by Ranganathan (1931) and the guiding concepts of fast-growing companies within a small margin of time, startups known as “unicorns”, especially Joseph Schumpeter’s theory of creative destruction (1911). The general objective of this work is to research the construction of an DL in the base service of Spotify streaming users, the object of this research's case study. Added to it are the following specific objectives: researching the area of Knowledge Representation in Information Science (CI), where LDs are inserted; analyze the context of the research object with studies on “unicorn” companies, the musical database of users from Fortaleza, in addition to the Five Laws of Ranganathan and present the proposal for an LD in the database services of Spotify users from Fortaleza. For this, the research has characteristics of a bibliographic and descriptive nature to assist in understanding the guidelines that operate in the relationship between the user and sound information within the CI, also observing the importance of understanding this user's profile. It also uses the Integrated Methodological Model for Thesaurus Construction” developed by Cervantes (2009) and the thesis by professor Heliomar Cavati Sobrinho (2014) for the construction of Documentary Language and the collection of terms is carried out in three streaming playlists of music. It is concluded from what was worked on that there is an intersection between Ranganathan's laws and Joseph Schumpeter's theory of creative destruction in streaming services, with this relationship being observed in the business model and the similarities in the form of organization, cataloging and recovery of musical information applied in these services with that based on documentary representation, as demonstrated at the end of the work with the construction of the thesaurus with Fortaleza terms in order to be replicated in different regional terms, which can facilitate personalized searches on streaming services.